Nature Inc. Environmental Conservation in the Neoliberal Age - Büscher, Bram; Dressler, Wolfram; Fletcher, Robert (University of Arizona Press, 2014)
With global wildlife populations and biodiversity riches in peril, it is obvious that innovative methods of addressing our planet's environmental problems are needed. But is "the market" the answer? Nature™ Inc. brings together cutting-edge research by respected scholars from around the world to analyze how "neoliberal conservation" is reshaping human-nature relations.